If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8 = 116 + -6x Reorder the terms: 8 + 6x = 116 + -6x Solving 8 + 6x = 116 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 8 + 6x + 6x = 116 + -6x + 6x Combine like terms: 6x + 6x = 12x 8 + 12x = 116 + -6x + 6x Combine like terms: -6x + 6x = 0 8 + 12x = 116 + 0 8 + 12x = 116 Add '-8' to each side of the equation. 8 + -8 + 12x = 116 + -8 Combine like terms: 8 + -8 = 0 0 + 12x = 116 + -8 12x = 116 + -8 Combine like terms: 116 + -8 = 108 12x = 108 Divide each side by '12'. x = 9 Simplifying x = 9
| 5+6y+9y=15+5 | | 6+11x=46+x | | a^2+5a=36 | | 6+5x=46+x | | 1x*4x=150 | | 49=6x-5 | | 7x+3+2=16+3 | | 2x-5=9x-25 | | (1x)(4x)=1500 | | 26x(x+3)=3380 | | (1x)(4x)=1 | | 8+8x=85+x | | 5x-7=38 | | 3x=2x+18 | | 6x+28=13x-28 | | -19-5X=5-9X | | 17+n=14+3 | | x^4+5x^3+20x^2+60x=-116 | | -8+5x=-12x-1 | | 111-5X=10X+21 | | 10x-29=51 | | 5X+12=93+4X | | 8+11X=98+X | | 5x+13y=126 | | 2(3+3x)=6x+6 | | 2x+3x+6=10x-16 | | 3x+5y=70 | | 6x+31=14x-65 | | 4(x-8)=25.6 | | 6(a+1)=58.2 | | 6(a+1)= | | 8A+8B=-16 |